PWE-074 Factors that predict severe Clostridium difficile infection (CDI). (28th May 2012) - Sugumaran, A; Eisa, M; Musiime, G; Mendes, F; Khan, H; Cefai, C
Abstract : Introduction: Clostridium difficile is a well-recognised infective cause for increased morbidity and mortality especially in hospitalised patients. 1 "Severe" CDI as defined by Health Protection Agency (HPA) is infection with stool positive for toxin, with white cell count >15×10 9 /l, or an acute rising serum creatinine (ie, >50% increase above baseline), or a temperature of >38.5°C, or evidence of severe colitis (abdominal or radiological signs). Increasing age, female sex, prolonged hospital stay, patient movement between wards, previous CDI, usage of proton pump inhibitors (PPI), histamine blockers (H2B) and antibiotics were reported to be associated with CD infection and colonisation, 2 3 but our aim was to check if the above factors predicted the severity of the infection. Methods: Data were collected from 392 patients who were diagnosed with CDI between January 2010 and December 2011. The CDI team (one Consultant, two nurse practitioners, one pharmacist) normally review patients twice weekly in our district general hospital. Details on the above risk factors were noted to study the correlation with severity of infection. Results were analysed with Pearson correlation test. Results: At the time of diagnosis, out of 392 patients, 206 were classified as "mild, " 76 "moderate, " 91 "severe" and 3 "life-threatening" infection (severity not documented in 16). Age distribution varied between 22 and 100 years, with 153 male and 239 female patients. 316 patients were on atleast one antibiotic when they developed CDI, chest infection being the commonest indication (36.8%). Amoxicillin was the most used antibiotic and the range of days on antibiotic varied between 1 day and long term usage (>3 years). 46% of patients were taking PPI while only 7.8% were on H2Bs. There were upto maximum four ward transfers and average of 17.62 inpatient days before CDI. Pearson correlation test showed there is no significant association between severity and any of the identified risk factors, closest being previous CD infection (p=0.058). Conclusion: Though there are definite risk factors associated with development of CDI, our study confirms that none correlate with the severity. More research is needed to clarify factors that will help identify hospitalised patients at risk of developing severe CDI. Competing interests: None declared. References: 1. Leffler DA, Lamont JT. Editorial: not so nosocomial anymore: the growing threat of community-acquired Clostridium difficile. Am J Gastroenterol 2012;107 :96–8. 2. Johnson S . Recurrent Clostridium difficile infection: a review of risk factors, treatments and outcomes. J Infect 2009;58 :403–10. 3. Loo VG, Bourgault A, Poirier L, et al. Host and Pathogen factors for CD infection and colonization. N Engl J Med 2011;365 :1693–703.